Learning in a digital age - Capstick, Shirelle (My University, 2017)
I will endeavour to express my view that using digital media has helped me in my studies. Using digital tools alongside typical techniques of study allows for a broader range of view on a subject. Not only does it allow a greater research base for information but it also offers different points of view that can be used for clarification or clearer understanding.
Presented on April 24, 2017 at Student Research Day held at MacEwan University in Edmonton, Alberta.